2011
DOI: 10.1182/blood-2010-05-287565
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of human fetal blood stem cells in the osteogenesis imperfecta mouse leads to improvement in multiscale tissue properties

Abstract: Osteogenesis imperfecta (OI or brittle bone disease) is a disorder of connective tissues caused by mutations in the collagen genes. We previously showed that intrauterine transplantation of human blood fetal stem/stromal cells in OI mice (oim) resulted in a significant reduction of bone fracture. This work examines the cellular mechanisms and mechanical bone modifications underlying these therapeutic effects, particularly examining the direct effects of donor collagen expression on bone material properties. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
80
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(99 citation statements)
references
References 52 publications
19
80
0
Order By: Relevance
“…Sex-dependent differences in skeletal muscle development in these mice were also noted [18]. Increased mineral-to-matrix ratio in the males is consistent with the increased density reported in younger oim/oim males in the same background [36], studied here. Increased mineral-tomatrix ratio observed in both genders of oim/oim mice indicates a lower matrix content rather than excessive mineralization.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Sex-dependent differences in skeletal muscle development in these mice were also noted [18]. Increased mineral-to-matrix ratio in the males is consistent with the increased density reported in younger oim/oim males in the same background [36], studied here. Increased mineral-tomatrix ratio observed in both genders of oim/oim mice indicates a lower matrix content rather than excessive mineralization.…”
Section: Discussionsupporting
confidence: 87%
“…Rao et al [33] also found gender differences in response of pamidronate-treated oim/oim mice with females showing a greater reduction in bone length in response to higher doses. Vanleene et al [36] also found that female human fetal bone stem/stromal cell transplantation into male and female oim/oim mice responded differently with females showing an increase in carbonate content and males an increase in crystallinity.…”
Section: Discussionmentioning
confidence: 97%
“…Transplanted e-CSC homed to areas of bone growth and fracture repair and expressed osteoblast differentiation genes Osteopontin and Osteocalcin and the COL1A2 protein, indicating their differentiation to functional osteoblasts. These findings are in agreement with previous studies in the oim model that demonstrated the direct differentiation of transplanted cells to osteoblasts [13][14][15][16] and subsequent improvements in disease pathology. In addition, we used the detection of human factor IX as an immunoassay to detect the presence of mouse anti-human antibodies in the serum of mice transplanted with human cells and we were able to show the absence of immune reaction against allogeneic cells.…”
Section: Discussionsupporting
confidence: 83%
“…These results are in line with our previous studies [15,16,62]. Fracture reduction in e-CSC transplanted mice was attributed to an increase in bone plasticity, as previously demonstrated [23], and greater bone ductility.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation